El índice de inseguridad lingüística en la radio local almeriense - López González, Antonio María (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2005)
The linguistic confidence rate provides us with information about the level of convergence or divergence between the sociolinguistic consciousness and the performance inside a speech community. This causes the stabilization of the linguistic varieties, when the coincidence occurs, or the linguistic change, in the case of discrepancy. For the analysis of the linguistic confidence, it is necessary to compare the attitude to the linguistic performance. This phenomenon is what this article aims at: To show and to analyze the correlation between the journalists' sociolinguistic attitude and the performance during the daily local broadcasting in Almeria (Spain).
The linguistic confidence rate in the local Almeria radio